Engaging Critical Pedagogy in the Current English Language Classroom: Challenges and Opportunities - Bohara, Dipak Kumar (Journal of NELTA Karnali, 2024)
As the world becomes increasingly diverse and interconnected, the importance of cultivating critical perspectives and communication skills in language education is paramount. This study aims to investigate the challenges encountered by teachers and learners in implementing critical pedagogy while exploring the potential benefits it can bring to the language learning process. Drawing on the secondary source of data, the paper offers insights into strategies for addressing challenges and maximising opportunities for a transformative and inclusive ELT classroom. Furthermore, the paper scrutinises the adaptability of Critical Pedagogy to diverse cultural and linguistic contexts, emphasising its potential to enhance language proficiency while nurturing socially responsible global citizens. Practical strategies for educators are discussed, including the incorporation of inclusive materials, fostering dialogue, and promoting student agency. By addressing the challenges head-on and harnessing the opportunities presented, this paper focuses on the meaningful integration of Critical Pedagogy in the English language classroom, promoting a more reflective and socially conscious approach to language education in the current landscape of English language teaching in Nepal.